2015
DOI: 10.1007/s13187-015-0966-1
|View full text |Cite
|
Sign up to set email alerts
|

Results from an Evaluation of the Georgia Colorectal Cancer Control Program’s Community Education and Outreach Events, 2013

Abstract: Although public health practitioners commonly use community education and outreach events to promote cancer screening, the effectiveness of this strategy remains unclear. This study evaluated 23 outreach events, conducted as part of the Georgia Colorectal Cancer Control Program. Of the estimated 1778 individuals who attended these events, those ages 50-75 were eligible to participate in a telephone survey 3 months after attending an event. Surveys measured colorectal cancer (CRC) risk status, CRC screening his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Eight studies used flipcharts to aid awareness and screening education (n = 7 both, n = 1 awareness) although, did not report findings on flipcharts ( Molokwu et al, 2017 , Tong et al, 2017 , Mojica et al, 2016 , Briant et al, 2018 , Chow et al, 2020 , Cassel et al, 2020 , Jo et al, 2017 , Cuaresma et al, 2018 ). Similarly, nine studies used brochures to aid education (n = 1 screening, n = 1 awareness, n = 7 both) although, only five reported brochure-specific findings (findings discussed in this section and below) ( Dominic et al, 2020 , Woodruff et al, 2017 , Naguib et al, 2017 , Jo et al, 2017 , Nguyen et al, 2017 , Cuaresma et al, 2018 , Christy et al, 2016 , Fransen et al, 2017 , Mukherjea et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies used flipcharts to aid awareness and screening education (n = 7 both, n = 1 awareness) although, did not report findings on flipcharts ( Molokwu et al, 2017 , Tong et al, 2017 , Mojica et al, 2016 , Briant et al, 2018 , Chow et al, 2020 , Cassel et al, 2020 , Jo et al, 2017 , Cuaresma et al, 2018 ). Similarly, nine studies used brochures to aid education (n = 1 screening, n = 1 awareness, n = 7 both) although, only five reported brochure-specific findings (findings discussed in this section and below) ( Dominic et al, 2020 , Woodruff et al, 2017 , Naguib et al, 2017 , Jo et al, 2017 , Nguyen et al, 2017 , Cuaresma et al, 2018 , Christy et al, 2016 , Fransen et al, 2017 , Mukherjea et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies used LCHEE for awareness interventions ( Boutsicaris et al, 2021 , Miguel et al, 2020 , Portilla-Skerrett et al, 2019 , Molina et al, 2018 , Holt et al, 2019 , Maxwell et al, 2019 , Maxwell et al, 2020 , Jenkins et al, 2022 , Molokwu et al, 2017 , Warner et al, 2019 , Dominic et al, 2020 , Gray et al, 2021 , Ou et al, 2019 , Tong et al, 2017 , Woodruff et al, 2017 , Mojica et al, 2016 , Parker et al, 2021 , Cassel et al, 2020 , Jo et al, 2017 , Nguyen et al, 2017 , Cuaresma et al, 2018 , Lucas et al, 2021 ). Nineteen studies showed improvements although, the findings of three were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…We learned that, in 2013, the Georgia Center for Oncology Research and Education became one of the CRC Control Program (CRCCP) awardees. Funded by the Centers for Disease Control and Prevention, the CRCCP has improved screening rates, demonstrating the effectiveness of implementing interventions to improve the overall care delivery of CRC screening services 19,20 . These multipronged efforts in improving cancer control are well illustrated by county‐level changes in screening for all three cancers from 2010 to 2018, using the Behavioral Risk Factor Surveillance System and National Health Interview Survey data (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…We observed significantly reduced risks of late-stage diagnosis among non-Hispanic White patients with BC in improve the overall care delivery of CRC screening services. 19,20 These multipronged efforts in improving cancer control are well illustrated by county-level changes in screening for all three cancers from 2010 to 2018, using the Behavioral Risk Factor Surveillance System and National Health Interview Survey data (Figure 3). 21,22 Although county-level changes in BC screening seem comparable between Ohio and Georgia (Figure 3B), we observed a substantial increase in CRC screening in rural counties in Georgia (Figure 3A).…”
Section: Breast Cancermentioning
confidence: 99%
“…Prior studies have evaluated outreach educational activities and reported that, although they provided insufficient evidence about their effectiveness in increasing screening rates, they led to improvement in CRC knowledge, attitudes, and intentions to secure CRC screening. 14 The results of this CRC educational campaign, which incorporated the use of a giant inflatable colon and focused on raising awareness about CRC and its screening and prevention, would certainly add to the extensive research examining the importance of community educational campaigns as a potential strategy for CRC prevention.…”
Section: Discussionmentioning
confidence: 99%